Illicit enrichment : a guide to laws targeting unexplained wealth - Dornbierer, Andrew (Basel Institute on Governance, 2021)
"Provides a comprehensive guide to illicit enrichment laws and their application to target unexplained wealth and recover proceeds of corruption and other crimes. The open-access book covers both criminal and civil-based laws from around the world. Investigators, prosecutors, legislators and academics alike will benefit from the clear descriptions and practical guidance on different approaches to targeting unexplainable increases in wealth, how to establish cases in court, and common legal challenges to illicit enrichment laws." About this publication